1991
DOI: 10.1093/ajcn/53.1.314s
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin E in preventing the oxidation of low-density lipoprotein

Abstract: The fatty acid composition, antioxidants, and the oxidation resistance of the low-density lipoproteins (LDL) from a number of different donors were determined. The oxidation resistance of LDL, as determined in vitro by the duration of the lag-phase in copper ion-induced oxidation, did not correlate with the alpha-tocopherol content of the LDL. By supplementating plasma with vitamin E, the alpha-tocopherol content of LDL could be increased from approximately 9 to 30 mol/mol LDL and also the oxidative resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
255
1
7

Year Published

1992
1992
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(274 citation statements)
references
References 17 publications
11
255
1
7
Order By: Relevance
“…Plasma was prepared by centrifugation and used immediately. For enrichment of LDL with the various vitamin E isomers [20], separate aliquots of plasma (5 ml) were supplemented with 400 gtl of DMSO (control) or stock solution of either ~-, y-and ~-TOH, incubated for 6 h at 37°C, before LDL was isolated by the 2 h ultracentrifugation method using the TL100.4 rotor [21]. Excess KBr and remaining water-soluble antioxidants were then removed from the LDL by gel filtration using a single PD-10 column (Pharmacia, Uppsala, Sweden).…”
Section: Preparation Of Native and Tocopherol-enriched Ldlmentioning
confidence: 99%
“…Plasma was prepared by centrifugation and used immediately. For enrichment of LDL with the various vitamin E isomers [20], separate aliquots of plasma (5 ml) were supplemented with 400 gtl of DMSO (control) or stock solution of either ~-, y-and ~-TOH, incubated for 6 h at 37°C, before LDL was isolated by the 2 h ultracentrifugation method using the TL100.4 rotor [21]. Excess KBr and remaining water-soluble antioxidants were then removed from the LDL by gel filtration using a single PD-10 column (Pharmacia, Uppsala, Sweden).…”
Section: Preparation Of Native and Tocopherol-enriched Ldlmentioning
confidence: 99%
“…TOH is transported in plasma by lipoproteins (Traber et al, 1993). In vitamin E supplemented low density lipoprotein (LDL), oxidative resistance is signi®cantly enhanced (Esterbauer et al, 1991). The TOH content of membranes may be the most important factor in determining the susceptibility of microsomes, LDL, hepatocytes or whole organs to ROS-mediated peroxidative damage (Di Mascio et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Leukocyte adhesion was significantly reduced by pretreatment of the animals with superoxide dismutase, implying a key mediator role for superoxide radicals in CS-induced leukocyte/endothelium interaction (11). Indeed, studies by Pryor and coworkers (12, 13) have shown that CS (both gas-phase and particulate matter) introduces into the organism an abundance of reactive oxygen species (ROS), including superoxide radicals.The action of superoxide radicals and other ROS can be counteracted not only by superoxide dismutase, but also by the water-soluble antioxidant vitamin C (14-16), as well as by the lipid-soluble vitamin E and probucol, both ofwhich act as chain-breaking antioxidants and interfere with the process of lipid peroxidation (17,18). Probucol and the antioxidant vitamins C and E have been demonstrated to slow the progression of atherosclerosis in laboratory animals (19,20) and to reduce cardiovascular mortality in large epidemiological surveys (21-24).…”
mentioning
confidence: 99%
“…The action of superoxide radicals and other ROS can be counteracted not only by superoxide dismutase, but also by the water-soluble antioxidant vitamin C (14-16), as well as by the lipid-soluble vitamin E and probucol, both ofwhich act as chain-breaking antioxidants and interfere with the process of lipid peroxidation (17,18). Probucol and the antioxidant vitamins C and E have been demonstrated to slow the progression of atherosclerosis in laboratory animals (19,20) and to reduce cardiovascular mortality in large epidemiological surveys (21)(22)(23)(24).…”
mentioning
confidence: 99%